(untitled) (Al-Farooq Journal of Sciences, 2026)
This study was conducted on seven commercial drinking water desalination stations in the Msallata Municipality. water samples were collected during june (2026) using sterile (500 mL) plastic bottles. All Samples were properly Labeled and transported to the (Delta) Laboratory, wher Laboratory analyses were performed occording to standard analytical procedures. the obtained results were Compared with the Libran standard Specifications and world Health organization drin King water guidelines to assess compliance with drinking water quality standards. statistical analysis was carried out using the Statistical package For the social sciences. (spss) to calculate means, standard deviations, an (t- test) in order to evaluate significant differences between the analytical results and the Libyan and international drinking water standads. several important drinking water quality parameters were determined using standard methods and calibrated analytical instruments the results showed that the PH values of all studied water Samples complied with the drinking water standards. Calcium Concentrations were below the permissible Limits, while the Low chloride Concentrations resulted. in reduced water Salinity Magnesium and nitrate concentrations were also below the maximum. permissible Limits, Furthermore, Sulfate Concentrations were considerably Low, indicating that no adverse effects ON the taste of overall quality of the drinking water are expected. The study recommends Continuous periodic monitoring of drinking water quality, improving desalination and treatment processes, and conducting Future studies involving alarger number of desalination stations to ensure the Long- term sustainability of drinking water quality.